ANALISIS KINERJA DENGAN KONSEP KONVENSIONAL DAN KONSEP VALUE BASED TERHADAP RETURN SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2018 - Dina Huzriyah; Abdul Wahid Mahsuni; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine the performance analysis with conventional concepts and values based concepts in stock returns. The population in this study are food and beverage companies listed on the Indonesian stock exchange. The sampling technique was a purposive sampling technique, the sample chosen was 10 companies. Data retrieved using the documentation method. The data analysis method is multiple regression analysis by SPSS version 14 software (Product Statistics and Solution services version 14). The test data used is the simultaneous hypothesis test (f), the coefficient of determination (R2), and partial hypothesis test (t). The results of the study indicate that simultaneously the independent variables significantly influence the dependent variable. Based on the test results of the coefficient of determination, the adjusted R value was 30,0% while the remaining 70,0% was influenced by other variables not included in this study. Based on the partial results that the return on invesment and return on equity affect the stock returns, while the practice of operating cash flow and economic value added does not affect the stock returns. Keywords : Return On Invesment, Return on Equity, Operating Cash Flow, Economic Value Added and Stock Return